(untitled) (Scientific journal of the Fergana State University, 2025)
Pughead deformity has been recorded in various fish families inhabiting both natural and artificial water bodies. However, occurrences of this anomaly in natural populations remain relatively rare. This study reports a newly recorded case of pughead deformity in the Prussian carp, Carassius gibelio (Bloch, 1782), observed in ditch waters within the Fergana Region. The morphometric characteristics of the abnormal specimens were compared with those of normal individuals. In the deformed specimen, the upper jaw was shorter than the lower jaw, and the anterior part of the head was abruptly directed downward, resulting in a significantly reduced snout length. However, no noticeable differences were observed in meristic characteristics.